Arabizi (Franco) in Egypt: A Study of Features, Reasons, Attitudes, and Educational Influence among Youth in Online Communication - Wafa, Muhammad (AUC Knowledge Fountain, 2025)
This study explores the phenomenon of Arabizi (Franco) as it is employed by Egyptian youth in online communication, focusing on the sociolinguistic factors that influence language choice, particularly educational background. Through a mixed-methods approach, including quantitative analysis of an online questionnaire using inferential statistics and qualitative examination of text samples, this study investigates the most common language varieties used by Egyptian youth, the underlying reasons for Arabizi's adoption, attitudes towards its usage, and the salient features of this variety of online communication. The findings reveal that Arabizi is widely used among Egyptian youth from all educational backgrounds. It is especially common among those who graduated from national and international schools. The Egyptian youth’s primary reasons for using Arabizi include its speed, convenience, ease of typing, and its role as a communication code among peers, symbolizing a distinct generational identity. Additionally, the study uncovers significant differences in language preferences based on educational background, with international school graduates more likely to use Arabizi and English in online communication, while governmental school graduates prefer Egyptian colloquial Arabic. The study also found that attitudes towards Arabizi vary according to educational background, with the majority of international school graduates generally viewing it more positively, appreciating its efficiency and modernity, while some governmental school graduates expressed concerns about its impact on Arabic language and identity. The findings of the study indicate that the distinctive linguistic features of Arabizi, as utilized by Egyptian youth in online communication, largely mirror the general characteristics of Arabizi observed in other Arab countries. However, a key distinction in the Egyptian context is the relatively lower degree of code-switching with English. The results contribute to the understanding of language variation in the digital age, emphasizing the impact of globalization on language practices and the ongoing tension between linguistic change and cultural preservation. This research provides valuable insights into the dynamic linguistic landscape of Egyptian youth, offering implications for future studies on language use in Arab-speaking communities. keywords: Arabizi, Language Variation, Educational Background, Digital Communication, attitudes, Reasons.